Microbiological quality of spices marketed in the city of Botucatu, Sao Paulo, Brazil - Moreira, P. L. [UNESP]; Lourencao, T. B. [UNESP]; Pinto, J. P.A.N. [UNESP]; Rall, V. L.M. [UNESP] (Elsevier, 2009)
The aim of this work was to assess the microbiological quality of spices sold in Botucatu, Sao Paulo, Brazil. A total of 233 samples were analyzed for mesophilic bacteria, thermotolerant coliforms, Bacillus cereus, Staphylococcus aureus, and Salmonella. Data showed that 21 and 5.6% of these samples were not in agreement with the standards of Brazilian law, due to an excess of coliforms and to the presence of Salmonella, respectively. Black pepper and cumin exhibited the lowest microbiological quality, whereas bay leaf showed the highest quality. It was concluded that the seasonings possessed poor microbiological quality, and new alternatives should be taken in the primary production in order to improve this quality. Irradiation may also be a tool to assure the safety of these products. Copyright ©, International Association for Food Protection.